The Risk Factors of Obesity Among Elderly in Sintang, Indonesia - Abil Rudi; Novin Yetiani (Publisher Cv. Inara, 2021)
Body Mass Index problem is becoming a double burden in Indonesia, including among older people. Nowadays, the elderly face a high index of BMI due to some risk factors and it is leading to other non-communicable diseases. This research aimed to examine the correlation between some determinants and obesity among older people in Sintang Regency, West Kalimantan. 358 elderly aged 46 to 65 years participated in this study selected by the total sampling method. The independent variables in this study were knowledge, activity, food intake, sex, attitude, age, the history of obesity, and obesity breeds, type contraception, and the duration of sleep. The multivariate analysis was found that knowledge, activity, food intake, age, and duration of sleep were significantly associated with obesity among the elderly. The preventive and promotive approach is needed to treat the obesity prevalence.